Improvement of Genetic Transformation Efficiency in Vanda tricolor Orchid Using Acetosyringone - Rindang Dwiyani; Azis Purwantoro; Ari Indrianto; Endang Semiarti (ANNALES BOGORIENSES, 2010)
Vanda tricolor  Lindl. var. suavis  is an Indonesian wild orchid which is now extremely rare in nature due to its habitat  destruction.  Development  of  an  appropriate  method  for  improving   Vanda  orchid  through  genetic modification could be valuable for horticulture and, indirectly, also for conservation. In this research, a method of  Agrobacterium-mediated transformation of two  Vanda  tricolor  obtained  from  Salak Mount, West Java and merapi Mount, Yogyakarta in Indonesia protocorms was improved using acetosyringone (AS). Concentrations of 0 and 25 ppm AS were used in transformation of pG35S binary vector containing kanamycin resistance gene into V.  tricolor  protocorms.  The  result  showed  that  25  ppm  AS  was  required  on  innoculation  with Agrobacterium  solution, without AS on cocultivation. Five week s after  treatment  on the 300  ppm kanamicyncontaining medium, green protocorms were obtained, that  was  11.01% for  V.  tricolor  from Salak Mount with pre-culture treatment prior to innoculation, 9.39% for  V.  tricolor  from Merapi  Mount with pre-culture treatment prior to  innoculation,  and  1.37%  for  V.  tricolor  from  Merapi  Mount  without  pre-culture  treatment  prior  to innoculation. The  best  condition  to  set  high  efficiency  of  transformation  is  pre -culture  protocorms  prior inoculation, soaking protocorm on 25  ppm  AS for 30 minutes, then cocultivate its on AS-free  callus induction medium Key words: Vanda tricolor, Agrobacterium, orchid protocorms, acetosyringone